2011
DOI: 10.1007/s13205-011-0037-1
|View full text |Cite
|
Sign up to set email alerts
|

Current methods in structural proteomics and its applications in biological sciences

Abstract: A broad working definition of structural proteomics (SP) is that it is the process of the high-throughput characterization of the three-dimensional structures of biological macromolecules. Recently, the process for protein structure determination has become highly automated and SP platforms have been established around the globe, utilizing X-ray crystallography as a tool. Although protein structures often provide clues about the biological function of a target, once the three-dimensional structures have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 224 publications
0
22
0
Order By: Relevance
“…Moreover, studies have demonstrated the importance of mechanical responses, structure, and biological functions of human tissues in understanding diseases such as arthritis, atherosclerosis, and asthma . The fields of structural proteomics permits high‐throughput determination of atomic resolution of hair protein structure on a genome‐wide scale . It also permits high‐throughput automated determination of structure and annotation of individual hair protein components and the complexes they form .…”
Section: Structural Proteomics Of Hairmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, studies have demonstrated the importance of mechanical responses, structure, and biological functions of human tissues in understanding diseases such as arthritis, atherosclerosis, and asthma . The fields of structural proteomics permits high‐throughput determination of atomic resolution of hair protein structure on a genome‐wide scale . It also permits high‐throughput automated determination of structure and annotation of individual hair protein components and the complexes they form .…”
Section: Structural Proteomics Of Hairmentioning
confidence: 99%
“…It also permits high‐throughput automated determination of structure and annotation of individual hair protein components and the complexes they form . Beside MS based structural proteomics methodologies, other approaches such as NMR (for structures <25 KDa) and X‐ray crystallography can be used for high atomic resolution structure determination . An NMR‐based method known as transverse relaxation optimized spectroscopy can be used to identify structure of proteins around 50 KDa by means of pulsed sequences .…”
Section: Structural Proteomics Of Hairmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid increase in the number of experimentally-determined protein structures over the last three decades [15, 16] has significantly enabled protein structure prediction capabilities. Perhaps, the simplest conception is to use sequence homology based on comparisons to known structures to infer structural elements for proteins of interest [1719].…”
Section: Introductionmentioning
confidence: 99%
“…1 Even once a condition for protein crystallization is identified, not all crystals will be of high quality, meaning single and well-ordered crystals that diffract to suitable resolution with low mosaicity. Common methods to crystallize proteins include vapor diffusion, batch crystallization, and seeding.…”
mentioning
confidence: 99%